A Pilot Study of the Impact of NHS Patient Transportation on Older People with Dementia. (10th May 2010) - Roberts, Nicola; Curran, Stephen; Minogue, Virginia; Shewan, Jane; Spencer, Rebecca; Wattis, John
Abstract : Background . A pilot study using a mixed methodology was used to evaluate the effects of travelling on NHS Patient Transport Service ambulances on the experience of patients with dementia. The study assessed the feasibility of using Dementia Care Mapping in this setting and looked at the effects of the presence of designated staff teams on journeys, compared to journeys without such designated staff. Method . Dementia Care Mapping was used to observe and record participants' behaviour, mood, and engagement during their outward and return journeys to NHS hospital sites. Observations were analysed for themes relating to the effects of travelling on PTS across the two groups. Results and Conclusions . Participant's observed mood scores did not differ significantly across the two groups but the range of behaviours recorded on the escorted group journeys did and were reflective of formal care environments. The findings from this study highlight the importance of trained escorts on NHS PTS ambulances for people with dementia and provide important information regarding further research in this area.